Similarity considerations for scale-down model versus prototype on impact response of plates under blast loads. (March 2017) - Kong, Xiangshao; Li, Xiao; Zheng, Cheng; Liu, Fang; Wu, Wei-guo
Highlights: Corrected similarity of dynamic responses of geometrically incomplete scale-down mode of plate under blast load was studied. A well-suited method to determine the mass of TNT in the scale-down experiment was proposed. A rapid solution to predict the value of exponent n of correct similarity is proposed. Abstract: Due to the influence of strain-rate effect of rate dependent materials, the relations of responses between scale-down model and prototype plates under blast loads cannot assure the satisfaction of the scaling laws, which is known as non-scalability of structure under impact loads. In this paper, by employing the dimensional analytical method, the strain-rate effect involved in blast loaded plates with different scaled values was firstly analyzed, then a corrected equation was established by taking a correction factor of impulse per unit area into consideration. Besides, a set of empirical formulae used to calculate the impulse per unit area is given, in which the relations between the mass of TNT, the stand-off distance and the impulse per unit area is determined. Furthermore, this paper adopted the method presented by Oshiro and Alves [14] to establish the corrected similarity relation between incomplete scale-down models and prototype. On the basis of this, a rapid solution to predict the value of exponent n is proposed, guaranteeing this method could be used more smoothly in practical engineering.